A DISCUSSION OF THAI STUDENT TEACHERS’ EXPERIENCES OF CULTURE SHOCK DURING THEIR STUDY IN INDONESIA - Fitriana, Dinda; Pradita S.S., M.Hum, Intan (Wiralodra English Journal, 2020)
Culture shock aspect is such a common issue that is experienced among students who studyabroad. The causes of culture shock aspect usually are anxiety and the lack of interculturalcommunication competence. Most of studies in the previous study tend to discuss the importanceof intercultural communication competence and only describe the kinds of culture shock. Thus,to fill this empirical void, this study aims to investigate Thai student teachers’ experiences ofintercultural communication competence and how they handle their culture shock during study inIndonesia. In order to understand more about culture shock aspects, we used culture shock andaxiety theory by Oberg (1960) and Dörnyei (2005). The study is employed qualitative method.Participants in this research were two Thai student teachers who have lived for more or less 4years in one of Islamic universities in Yogyakarta., They are from different batch and major. Thedata were obtained by in-depth interview. We analyzed the data by using thematic analysismethod by Braun & Clarke (2006). The finding showed that all participants experienced theculture shock symptoms stages, such as tension of adaptation, sense of loss and rejection fromenvironment, rejected by new culture, unpredictable anxiety, and feeling of helplessness at thefirst time they studied in Indonesia. There was also an interesting finding that both of them hadthe lack of intercultural communication competence, and also the anxiety leads them to survivein Indonesia. Keywords: Culture Shock Symptoms, Intercultural Communication Competence, Anxiety